2020
DOI: 10.1515/spircare-2018-0065
|View full text |Cite
|
Sign up to set email alerts
|

Religious belief as a resilience factor in a long-term refugee setting at the Thai-Myanmar Border, Southeast Asia

Abstract: AbstractReligion has always had an influence on the causal attribution of people, i.e. how is your own destiny, happiness and misfortune interpreted? Since religious belief is not static, it is strongly influenced by the experiences that sufferers have gained in their past. It therefore plays an important role in dealing with trauma and stress in humanitarian crises – especially in vulnerable populations (such as refugees) and can be a source of power in difficult times. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This result is confirmed by another recent and extensive systematic review and meta-analysis, summarizing 34 observational studies and revealing a moderate correlation between religion/spirituality and resilience defined as “the ability to recover or cope with adverse situations” [ 12 ]. Other studies highlight the positive role religion plays in that process [ 13 , 14 , 15 , 16 , 17 , 18 ]. Usually, these studies relate to displaced populations from poor areas and diverse religious backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…This result is confirmed by another recent and extensive systematic review and meta-analysis, summarizing 34 observational studies and revealing a moderate correlation between religion/spirituality and resilience defined as “the ability to recover or cope with adverse situations” [ 12 ]. Other studies highlight the positive role religion plays in that process [ 13 , 14 , 15 , 16 , 17 , 18 ]. Usually, these studies relate to displaced populations from poor areas and diverse religious backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…This is because reliance upon God breeds resilience and enables them to make sense of their suffering (e.g. Pertek 2022;Atari-Khan et al 2021;Lusk et al 2021;Kaiser et al 2020;Choi & Hastings 2019;Manning & Miles 2018;Tippens 2017). Other studies have found that traumatic experiences erode religiosity, and in some cases, could prompt people to abandon their faith (Leo et al 2021;Janoff-Bulman 1992).…”
Section: Introductionmentioning
confidence: 99%
“…To minimize the deleterious effects of this situation, many strategies are in use worldwide, such as support groups, online courses, use of social networks, web meetings, yoga practice, meditation, and other contemplative religious and spiritual activities [3]. Religious and spiritual beliefs have been used, long since, to deal with tough situations [4] and, through scientific literature is still not so clear about the role of spirituality and religiosity (S/R) in physical and mental health during the pandemic, previous studies seem to support its role in favorable health outcomes [5]. This article proposes a discussion about the physiopathological mechanisms of COVID-19 and how S/R could be useful in this context.…”
mentioning
confidence: 99%